2022
DOI: 10.1155/2022/5553212
|View full text |Cite
|
Sign up to set email alerts
|

Improper Estimation of Thermodynamic Parameters in Adsorption Studies with Distribution Coefficient KD (qe/Ce) or Freundlich Constant (KF): Considerations from the Derivation of Dimensionless Thermodynamic Equilibrium Constant and Suggestions

Abstract: Adsorption processes often include three important components: kinetics, isotherm, and thermodynamics. In the study of solid–liquid adsorption, “standard” thermodynamic equilibrium constant K Eq … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 112 publications
0
27
0
Order By: Relevance
“…This is because they directly applied the distribution constant K D ( q e / C e ) as KEqnormalo in Eqn (14) for calculating the thermodynamic parameters. The problem with applying K D for such calculations has been discussed in the literature 18 . Other authors reported low magnitudes of Δ G °, such as 1.32 kJ mol −1 for adsorbing phosphate by ground burnt patties 87 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because they directly applied the distribution constant K D ( q e / C e ) as KEqnormalo in Eqn (14) for calculating the thermodynamic parameters. The problem with applying K D for such calculations has been discussed in the literature 18 . Other authors reported low magnitudes of Δ G °, such as 1.32 kJ mol −1 for adsorbing phosphate by ground burnt patties 87 .…”
Section: Resultsmentioning
confidence: 99%
“…The derivation of the standard thermodynamic equilibrium constant (Ksans-serifEqnormalo; dimensionless) for the adsorption process in solid–liquid phases has been recently discussed by Lima et al 17 and Tran 18 . Ksans-serifEqnormalo is simply introduced as Eqn (14).…”
Section: Introductionmentioning
confidence: 99%
“…As explained by Tran, this parameter is not a true adsorption equilibrium constant, and thus it cannot be applied for calculating thermodynamic adsorption parameters. However, by combining eq with eqs and , we can express this parameter as follows: K normalF ( q max , α , m , s ) = q max · A ( α ) · m α / 2 true( s K true) α with K = 10 –2 bar kg –1/2 m 2 for gas adsorption and K = 4 × 10 –4 (mol/L) kg –1/2 m 2 for solution adsorption, when the pressures are expressed in units of bar and the concentrations are expressed in units of mol/L.…”
Section: Discussionmentioning
confidence: 99%
“…It is somewhat puzzling to note that, almost simultaneously, Radian et al studied such LSERs for a case involving 30 organic pollutants (including mainly pesticides and pharmaceutical compounds) adsorbed onto a clay–polycation nanocomposite, whose adsorption behavior was described by the Freundlich equation written in the following way: C ads = K normalF × C eq n and introducing an adsorption coefficient K D at a specific concentration as K normalD = C ads C eq = K normalF × C eq n 1 However, unfortunately, the correlation applying the Abraham solvation parameters model to the corresponding K D data (calculated at a very low concentration) is not satisfying; the authors explained that this can probably be because the LSER method was initially created for adsorption by a partitioning mechanism (where a linear Freundlich trend is observed, with n ≈ 1), although this is not the case in their study where 0.2 ≤ n ≤ 1.55 . As for us, according to a recent discussion paper, we consider that the K D parameter is not appropriate for the estimation of such correlation; moreover, with the units selected by the original authors ( C ads in mmol/kg; C eq in mg/L), K D should be presented in the cumbersome units of mmol L/(mg kg)!…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation